2017
DOI: 10.1002/mc.22660
|View full text |Cite
|
Sign up to set email alerts
|

Kctd20 promotes the development of non‐small cell lung cancer through activating Fak/AKT pathway and predicts poor overall survival of patients

Abstract: Kctd20 (potassium channel tetramerization protein domain containing 20) is a positive regulator of Akt signaling. However, the role of Kctd20 during the course of tumorigenesis and development is unclear. Using immunohistochemistry, we demonstrated that, in non-small cell lung cancer (NSCLC) patients, Kctd20 protein expression significantly correlates with advanced TNM stage (P < 0.001), positive status for regional lymph node metastasis (P = 0.019), and poor overall survival (P = 0.013). Proliferation and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, to the best of our knowledge, the role of KCTD20 in the development and progression of other types of cancer remains unclear. Consistent with a previous report on KCTD20 in NSCLC, the present study demonstrated that KCTD20 expression was upregulated in glioma tissues compared with in normal tissues ( 63 ). The present study demonstrated that miR-324-5p may bind directly to the KCTD20 3′-UTR to regulate its expression.…”
Section: Discussionsupporting
confidence: 93%
“…However, to the best of our knowledge, the role of KCTD20 in the development and progression of other types of cancer remains unclear. Consistent with a previous report on KCTD20 in NSCLC, the present study demonstrated that KCTD20 expression was upregulated in glioma tissues compared with in normal tissues ( 63 ). The present study demonstrated that miR-324-5p may bind directly to the KCTD20 3′-UTR to regulate its expression.…”
Section: Discussionsupporting
confidence: 93%
“…Further involvement of KCTD5 in other tumor types has not yet been described, but Brockmann and colleagues demonstrated that KCTD5 may switch off the Akt pathway, which regulates cell survival, cell cycle progression and cellular growth [ 112 ]. Furthermore, since the AKT pathway interplays with Hh signaling through the non-canonical pathway, it may be possible that KCTD5 alterations affect the Hh signaling-dependent tumorigenesis [ 113 , 114 ].…”
Section: Insides Into the Role Of E G H Groups And Other Kctd Proteins In Cancermentioning
confidence: 99%
“…with Alzheimer's risk (GWAS) 110 Degrades RhoA 33,76 Regulates apoptosis 120 Inhibits NF-κB and AP-1 118 Aa a tumor suppressor in nonsmall cell lung cancer 121 Poor prognosis if overexpressed in breast cancer 122 Overexpressed in osteosarcoma 123 16,96 ) Inhibits mTORC1 activity 14 Inhibits Hh pathway by degrading HDAC 12 Deletion/ reduced expression in medulloblastoma 94 Loss of heterozygosity in prostate adenocarcinoma 129 Reduced expression in hepatocellular carcinoma 130 (Continues) Inhibits transcription factor AP-2α 9 and Wnt signaling by degrading β-catenin 131 I27N mutation caused kidney dysfunction in mice 132 Missense mutations associated with scalp-ear-nipple syndrome 133 Other Regulates GABA B2 signaling 17,135,136 ND Other KCNRG ND Kv channel 139,140 Suppresses K + channel activity 139 Deleted in B-cell chronic lymphocytic leukemia, [140][141][142] prostate cancer 140 and multiple myeloma 142 Other KCTD18 ND ND ND Duplication of 2q33 in one patient with epilepsy, devel. delay, autistic behavior 143 Haplotype associated with restless legs syndrome 144 G KCTD20 ND ND Activates Akt 145,146 Gen var associated with insulin resistance (GWAS) 147 BTBD10 ND Akt1-3 148 Inhibits apoptosis, activates Akt 149,150 Sporadic amyotrophic lateral sclerosis 151…”
Section: Figurementioning
confidence: 99%